Method for improving lead and bismuth corrosion resistance of FeNiCrAlTiSix high-entropy alloy through pre-oxidation treatment

By generating dense Al2O3, TiO2 and Cr2O3 multi-layer oxide films on the surface of FeNiCrAlTiSix high-entropy alloy, the problem of insufficient corrosion resistance of high-entropy alloys in liquid lead-bismuth environments is solved, and the effect of significantly improving corrosion resistance and reducing the risk of oxide film shedding is achieved.

CN119876834APending Publication Date: 2025-04-25INST OF METAL RESEARCH - CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411815170.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing FeNiCrAlTiSix high-entropy alloy still has problems of invasion of liquid lead-bismuth and excessive growth of oxide films under service conditions, resulting in insufficient corrosion resistance.

Method used

The dense and uniform multi-layer oxide films of Al2O3, TiO2 and Cr2O3 are generated on the surface of FeNiCrAlTiSix high-entropy alloy by pre-oxidation treatment, which prevents the invasion of lead and bismuth and the rapid growth of the oxide film.

Benefits of technology

The resistance to liquid lead-bismuth corrosion of FeNiCrAlTiSix high-entropy alloy is significantly improved, effectively protecting the alloy matrix from erosion and dissolution by lead-bismuth, and reducing the risk of oxide film shedding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876834A_ABST
    Figure CN119876834A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of lead and bismuth corrosion resistant nuclear high-temperature structural materials, and particularly relates to a method for improving lead and bismuth corrosion resistance of a FeNiCrAlTiSix high-entropy alloy through pre-oxidation treatment. The high-entropy alloy comprises the following chemical components in atomic percent: 35%-55% of Fe, 20%-30% of Ni, 10%-20% of Cr, 5%-15% of Al, 1%-10% of Ti and 0%-5% of Si. According to the method, a uniform and compact Al2O3, TiO2 and Cr2O3 multi-layer protective oxidation film is generated on the surface of the FeNiCrAlTiSix high-entropy alloy in situ from inside to outside by regulating and controlling the oxidation temperature and the oxidation time in the air atmosphere, the pre-oxidation film can effectively prevent lead and bismuth from invading and the oxidation film from being rapidly thickened, and the lead and bismuth corrosion resistance of the FeNiCrAlTiSix high-entropy alloy is remarkably improved. The method is easy to operate, low in cost and excellent in effect, and technical support is provided for application of the nuclear high-entropy alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of high temperature structural materials for lead-bismuth corrosion-resistant nuclear applications, and specifically relates to a method for improving the quality of FeNiCrAlTiSi x Method for making high entropy alloys resistant to lead-bismuth corrosion. Background Art

[0002] As production continues to develop, energy demand is increasing, and human dependence on clean, efficient, and renewable nuclear energy is increasing. At present, nuclear power has developed into the fourth generation of reaction systems, among which lead-cooled fast reactors have gradually become one of the reactor types that are being focused on at home and abroad due to their high energy density, good intrinsic safety, and high nuclear fuel utilization efficiency.

[0003] Liquid lead-bismuth eutectic (LBE) is a coolant material for lead-cooled fast reactors. It has excellent properties such as good heat transfer capacity, excellent neutron economy, low chemical reactivity, and high boiling point. However, liquid lead-bismuth eutectic is highly corrosive to most traditional structural materials, mainly including liquid metal embrittlement (LME) and liquid metal corrosion (LMC). For example, traditional ferrite / martensitic steel undergoes liquid metal embrittlement at temperatures below 450°C, and the oxide layer thickens and falls off at temperatures above 500°C; austenitic steel undergoes severe Ni dissolution at temperatures above 500°C, resulting in material phase change and material failure.

[0004] Existing FeNiCrAlTiSi x High entropy alloys have good resistance to lead-bismuth corrosion, but there are still problems of LBE intrusion and excessive oxide film growth under service conditions. Therefore, how to further improve the corrosion resistance of high entropy alloys and control the growth rate of oxide films during service has become a difficult problem in the industry. Summary of the invention

[0005] The main purpose of the present invention is to provide a method for improving FeNiCrAlTiSi x A method for making a high entropy alloy resistant to lead-bismuth corrosion, the method forms a dense and uniform thin layer of Cr2O3, Al2O3 and TiO2 oxide film on the surface of the high entropy alloy, significantly improving the corrosion resistance of the alloy in high-temperature liquid lead-bismuth eutectic, and effectively protecting the alloy matrix from being corroded and dissolved by lead-bismuth during long-term service.

[0006] The present invention solves the technical problem by adopting the following technical solutions:

[0007] A method for improving FeNiCrAlTiSi by pre-oxidation treatment x Method for high entropy alloys to resist lead-bismuth corrosion, by atomic percentage, FeNiCrAlTiSi xThe chemical composition of high entropy alloy is as follows: Fe 35%~55%, Ni 20%~30%, Cr10%~20%, Al 5%~15%, Ti 1%~10%, Si 0%~5%;

[0008] The method is to pre-oxidize FeNiCrAlTiSi x A uniform and dense protective multilayer oxide film of Al2O3, TiO2 and Cr2O3 is formed on the surface of the high entropy alloy from the inside to the outside, which specifically includes the following steps:

[0009] (1) The pre-prepared FeNiCrAlTiSi x High entropy alloy sheets are cold deformed and heat treated;

[0010] (2) Using SiC sandpaper to remove surface oxide scale and defects from the alloy plate treated in step (1), and grinding to 2000 mesh;

[0011] (3) placing the alloy plate treated in step (2) in an air atmosphere, keeping it in air at 600-1000°C for 1-4 hours, and then air cooling it to room temperature, thereby completing the FeNiCrAlTiSi x Pre-oxidation treatment of high entropy alloys.

[0012] The above-mentioned pre-oxidation treatment improves the FeNiCrAlTiSi x A method for making a high entropy alloy resistant to lead-bismuth corrosion, wherein in step (1), the cold deformation treatment is to use a double-track rolling mill to press down 60% in multiple passes along a fixed direction at room temperature, and the pressing amount in a single pass is 10-15%.

[0013] The above-mentioned pre-oxidation treatment improves the FeNiCrAlTiSi x The invention discloses a method for making a high entropy alloy resistant to lead-bismuth corrosion. In step (1), the heat treatment process comprises annealing treatment and aging treatment, wherein: the annealing treatment comprises keeping the temperature at 900-1100° C. for 1-10 hours and air cooling to room temperature; the aging treatment comprises keeping the temperature at 550-800° C. for 1-500 hours and water cooling to room temperature.

[0014] The above-mentioned pre-oxidation treatment improves the FeNiCrAlTiSi x A method for making a high entropy alloy resistant to lead-bismuth corrosion, wherein a uniform and dense protective multilayer oxide film of Al2O3, TiO2 and Cr2O3 is generated on the surface of the high entropy alloy, wherein the thickness of the Al2O3 oxide film is 200 to 500 nm, the thickness of the TiO2 oxide film is 400 to 800 nm, and the thickness of the Cr2O3 oxide film is 0.8 μm to 1.0 μm.

[0015] The above-mentioned pre-oxidation treatment improves the FeNiCrAlTiSi xA method for making a high entropy alloy resistant to lead-bismuth corrosion. When the high entropy alloy contains Si, a uniform and dense SiO2 oxide film is generated after pre-oxidation treatment. The thickness of the SiO2 oxide film is 200 to 500 nm.

[0016] The above-mentioned pre-oxidation treatment improves the FeNiCrAlTiSi x A method for high entropy alloy to resist lead-bismuth corrosion, wherein the pre-oxidized high entropy alloy is heated to 550°C and the oxygen concentration is 1×10 -6 After being corroded for 3000h under the condition of wt.%, its surface still has a thin and dense multi-layer protective oxide film with a thickness not exceeding 5μm.

[0017] The above-mentioned pre-oxidation treatment improves the FeNiCrAlTiSi x The method for making a high entropy alloy resistant to lead-bismuth corrosion is preferably such that the thickness of the oxide film is 2 to 5 μm after corrosion for 3000 hours.

[0018] The above-mentioned pre-oxidation treatment improves the FeNiCrAlTiSi x A method for resisting lead-bismuth corrosion of a high entropy alloy is provided by pre-oxidizing the high entropy alloy at an oxygen concentration of 1×10 -3 ~1×10 -9 After being immersed in a static liquid lead-bismuth environment with a concentration of wt.% and a temperature of 350-600°C for 100-10000 hours, no intrusion of liquid lead-bismuth and no dissolution of matrix elements occurred.

[0019] The design concept of the present invention is:

[0020] Pre-oxidation is a surface protection treatment method. By keeping the alloy in a high temperature and oxidizing atmosphere for a certain period of time, a dense and uniform oxide film can be pre-formed on the alloy surface, thereby improving the corrosion resistance of the alloy. The present invention is the first to apply pre-oxidation treatment to the surface treatment of high entropy alloys to improve the alloy's lead-bismuth corrosion resistance. In an air atmosphere, by controlling the oxidation temperature and oxidation time, the FeNiCrAlTiSi x A uniform and dense multi-layer protective oxide film of Al2O3, TiO2 and Cr2O3 is generated in situ on the surface of the high entropy alloy from the inside to the outside (when the alloy contains Si, a SiO2 oxide film can also be generated), which effectively prevents the intrusion of lead and bismuth and the rapid growth of the oxide film, significantly improving the FeNiCrAlTiSi xThe corrosion resistance of high entropy alloy to lead and bismuth. The principle that the oxide films of Al2O3, TiO2, Cr2O3 and SiO2 can be generated in situ in sequence from the inside to the outside is that due to the different diffusion rates of elements, Si as a fast-diffusion element and Cr with a high matrix content preferentially generate SiO2 and Cr2O3 oxide films on the surface. The formation of continuous oxide films hinders the inward diffusion of O elements. As the concentration of oxygen diffused inward decreases, Ti and Al with higher affinity for O form dense and uniform TiO2 and Al2O3 oxide films.

[0021] In addition, the FeNiCrAlTiSi x High entropy alloy is a new type of lead-bismuth corrosion-resistant alloy independently developed and prepared. The design mechanism of its composition and content is as follows: the alloy uses Fe as the matrix element, and Ni is added to stabilize the face-centered cubic phase (FCC phase) while promoting the formation of the ordered body-centered cubic phase (B2 phase). The good plasticity of FCC is used to absorb the excess Ni into the B2 phase, effectively inhibiting the dissolution corrosion of Ni; Ti promotes the increase of vacancy concentration, which is conducive to the rapid diffusion of elements such as Al and Cr and the formation of oxide film, effectively improving the corrosion resistance of the alloy; the addition of Si element promotes the formation of Al2O3 oxide film with strong protectiveness, while reducing the activity of Cr, significantly reducing the critical Cr content required to prevent internal oxidation, and alleviating the oxidation corrosion of the alloy. The formation of multilayer oxide films such as Al2O3, TiO2, Cr2O3 and SiO2 effectively improves the lead-bismuth corrosion resistance of high entropy alloy.

[0022] Compared with the prior art, the advantages and benefits of the present invention are as follows:

[0023] 1. The pre-oxidation treatment method used in the present invention is x A multilayer oxide film of Al2O3, TiO2 and Cr2O3 with a thickness of less than 2μm is pre-formed on the surface of the high entropy alloy. The oxide film is thin, uniform and dense, with good adhesion and excellent stability. It effectively prevents the penetration of LBE during the static liquid lead-bismuth immersion process, significantly improving the corrosion resistance of the high entropy alloy.

[0024] 2. The pre-oxidation treatment method used in the present invention is FeNiCrAlTiSi x The oxide film pre-generated on the surface of the high-entropy alloy grows slowly. The thickness of the oxide film on the pre-oxidized high-entropy alloy does not exceed 5μm after 3000h of corrosion, which greatly reduces the risk of oxidation and provides a guarantee for practical application.

[0025] 3. Compared with traditional surface coating technology and surface treatment methods, the pre-oxidation treatment method adopted in the present invention has a stronger bonding force between the oxide film and the substrate. At the same time, this method is low-cost, simple to operate, and easy to control, and is expected to realize the industrial application of high-entropy alloys for nuclear use.

[0026] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the cross-sectional morphology after pre-oxidation treatment in Example 1 of the present invention.

[0028] Figure 2 This is the cross-sectional morphology after pre-oxidation treatment in Example 2 of the present invention.

[0029] Figure 3 The oxygen concentration is 1×10 -6 Cross-sectional morphology after corrosion in wt.% liquid lead-bismuth for 3000h.

[0030] Figure 4 The oxygen concentration is 1×10 -6 Cross-sectional morphology after corrosion in wt.% liquid lead-bismuth for 3000h.

[0031] Figure 5 Example 1 without pre-oxidation treatment. After pre-oxidation treatment, the oxygen concentration at 550°C was 1×10 -6 Cross-sectional morphology after corrosion in wt.% liquid lead-bismuth for 3000h.

[0032] Figure 6 Example 2 without pre-oxidation treatment. After pre-oxidation treatment, the oxygen concentration at 550°C was 1×10 -6 Cross-sectional morphology after corrosion in wt.% liquid lead-bismuth for 3000h. DETAILED DESCRIPTION

[0033] The following is a more detailed description of the specific embodiments of the present invention in conjunction with the accompanying drawings and examples, so that the scheme of the present invention and its advantages in various aspects can be better understood. However, the specific embodiments and examples described below are only for the purpose of illustration, rather than for limiting the present invention.

[0034] In the specific implementation process, the present invention provides a method for improving FeNiCrAlTiSi by pre-oxidation treatment. x A method for making a high entropy alloy resistant to liquid lead-bismuth corrosion, the chemical composition and specific preparation technology of the alloy are as follows:

[0035] 1. The chemical composition of high entropy alloys is as follows, in terms of atomic percentage:

[0036] Fe: 35% to 55%; Ni: 20% to 30%; Cr: 10% to 20%; Al: 5% to 15%; Ti: 1% to 10%; Si: 0% to 5%.

[0037] 2. The preparation and pre-oxidation treatment methods of high entropy alloys are as follows:

[0038] (1) Weighing metal raw materials with a purity greater than 99.95 wt.% according to a predetermined composition ratio, the chemical composition of the high entropy alloy is shown in Table 1, and preparing alloy ingots by vacuum arc melting 6 times, and then obtaining alloy plates by copper mold casting;

[0039] (2) The alloy plate is subjected to solution treatment and sealed with a vacuum quartz tube. The pressure in the quartz tube is 2×10 -3 Pa, solution treatment temperature is 1100℃, holding time is 2h, and water cooling is performed to room temperature;

[0040] (3) The alloy plate after the solution treatment is subjected to cold deformation and heat treatment. The cold deformation treatment is to use a double-track rolling mill to press down in a fixed direction for multiple passes at room temperature, with a pressing amount of 60% and a single-pass pressing amount of 10-15%. The heat treatment process is: annealing at 1000°C for 1 hour, air cooling to room temperature; aging at 700°C for 50 hours, and water cooling to room temperature;

[0041] (4) Cut a 15 mm × 12 mm × 1.5 mm specimen from the treated alloy plate, remove the surface oxide scale and some defects using SiC sandpaper, and grind to 2000 mesh (the sandpaper grinding sequence is as follows: 400 mesh → 600 mesh → 800 mesh → 1000 mesh → 1200 mesh → 1500 mesh → 2000 mesh), and remove surface stains from the polished sample using alcohol ultrasonic treatment;

[0042] (5) The polished sample is placed in an atmospheric atmosphere, kept at 800°C in air for 2 hours, and then cooled to room temperature in air to form a protective oxide film on the surface of the high entropy alloy, thereby completing the high entropy alloy pre-oxidation treatment and obtaining a pre-oxidized high entropy alloy sample.

[0043] Table 1 Chemical composition of high entropy alloy (at.%)

[0044] Fe Ni Cr Al Ti Si Example 1 50 25 13 8 4 0 Example 2 50 25 11 8 4 2

[0045] like Figure 1As shown, it can be seen from the cross-sectional morphology after the pre-oxidation treatment of Example 1 that a dense and continuous oxide film is generated on the alloy surface, and the surface oxide film has a uniform thickness, is complete and continuous, and is well bonded to the alloy matrix without falling off. A uniform and dense protective multilayer oxide film of Al2O3, TiO2 and Cr2O3 is generated on the surface of the high entropy alloy of Example 1 from the inside to the outside, with a thickness of 0.3 μm for Al2O3, 0.6 μm for TiO2, and 1.0 μm for Cr2O3.

[0046] like Figure 2 As shown, the cross-sectional oxide film formation of Example 2 by pre-oxidation treatment, through backscattered electrons (BSE) and X-ray energy chromatograph (EDS), it was observed that a dense and continuous oxide film was generated on the surface of the high entropy alloy; the oxidation product on the surface of the high entropy alloy was flat and continuous, and was well combined with the high entropy alloy matrix, and no shedding occurred. At the same time, the EDS element distribution showed that a dense Al2O3 oxide film was generated on the surface of the high entropy alloy, and it was observed that a uniform and dense TiO2, Cr2O3, and SiO2 oxide film structure was generated from the inside to the outside, with a thickness of 0.3μm for Al2O3, 0.5μm for TiO2, 0.9μm for Cr2O3, and 0.2μm for SiO2.

[0047] like Figure 3 and Figure 4 As shown, the pre-oxidized Example 1 and Example 2 were placed in a temperature of 550°C and an oxygen concentration of 1×10 - 6 wt.% liquid lead-bismuth eutectic was subjected to long-term immersion corrosion, and the cross-sectional morphology after 3000 hours of corrosion. No lead-bismuth intrusion was observed in the cross-section of Example 1 after pre-oxidation, and the surface of the high-entropy alloy was relatively smooth. The cross-sectional element distribution diagram showed that after 3000 hours of corrosion, the oxide film generated on the surface still had a continuous, complete, and dense structure, and the total thickness of the oxide film was 4.1μm. No lead-bismuth intrusion was observed in the cross-section of the corrosion sample of Example 2 after pre-oxidation treatment, and it had a continuous, complete, and dense oxide film structure. Figure 5 As shown in FIG. 1 , as a comparison, in the cross-sectional morphology of Example 1 without pre-oxidation treatment, lead-bismuth intrusion was observed in the cross section, with the maximum intrusion depth reaching 15 μm, and dissolution corrosion occurred in the high entropy alloy matrix; Figure 6 As shown in the cross-sectional morphology of Example 2 without pre-oxidation treatment, although the high entropy alloy did not have lead and bismuth intrusion, the oxide film grew too thick and there was a risk of falling off. Therefore, the pre-oxidation treatment significantly improved the FeNiCrAlTiSi x Liquid lead-bismuth corrosion resistance of high entropy alloys.

[0048] The implementation results show that the present invention canx The high entropy alloy is pre-oxidized to form a uniform and dense multi-layer protective oxide film of Cr2O3, Al2O3 and TiO2 with a thickness of less than 2 μm. After the pre-oxidized high entropy alloy is immersed in static liquid lead-bismuth for a long time (the high entropy alloy is immersed in an oxygen concentration of 1×10 -3 ~1×10 - 9 wt.%, and soaked in a static liquid lead-bismuth environment at a temperature of 350-600°C for 100-10000h), the integrity of the oxide film structure is still maintained, and the intrusion of liquid lead-bismuth and the dissolution of matrix elements do not occur, which effectively prevents the intrusion of lead-bismuth and the rapid growth of the oxide film, and significantly improves the lead-bismuth corrosion resistance of the high entropy alloy. The invention is simple to operate, low in cost, and easy to control, and provides a reference for the further industrial application of nuclear high entropy alloys.

[0049] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.

Claims

1. A method for improving FeNiCrAlTiSi by pre-oxidation treatment x A method for making a high entropy alloy resistant to lead-bismuth corrosion, characterized in that: In terms of atomic percentage, FeNiCrAlTiSi x The chemical composition of high entropy alloy is as follows: Fe35%~55%, Ni 20%~30%, Cr 10%~20%, Al 5%~15%, Ti 1%~10%, Si0%~5%; The method is to pre-oxidize FeNiCrAlTiSi x A uniform and dense protective multilayer oxide film of Al2O3, TiO2 and Cr2O3 is formed on the surface of the high entropy alloy from the inside to the outside, which specifically includes the following steps: (1) The pre-prepared FeNiCrAlTiSi x High entropy alloy sheets are cold deformed and heat treated; (2) Using SiC sandpaper to remove surface oxide scale and defects from the alloy plate treated in step (1), and grinding to 2000 mesh; (3) placing the alloy plate treated in step (2) in an air atmosphere, keeping it in air at 600-1000°C for 1-4 hours, and then air cooling it to room temperature, thereby completing the FeNiCrAlTiSi x Pre-oxidation treatment of high entropy alloys.

2. The method of claim 1 for improving FeNiCrAlTiSi by pre-oxidation treatment x A method for making a high entropy alloy resistant to lead-bismuth corrosion, characterized in that: In step (1), the cold deformation treatment is to use a double-track rolling mill to press down 60% in multiple passes along a fixed direction at room temperature, and the pressing amount in a single pass is 10-15%.

3. The method of claim 1 for improving FeNiCrAlTiSi by pre-oxidation treatment x A method for making a high entropy alloy resistant to lead-bismuth corrosion, characterized in that: In step (1), the heat treatment process includes annealing and aging, wherein: the annealing is carried out at 900-1100° C. for 1-10 hours and then air-cooled to room temperature; the aging is carried out at 550-800° C. for 1-500 hours and then water-cooled to room temperature.

4. The method of claim 1 for improving the FeNiCrAlTiSi x A method for making a high entropy alloy resistant to lead-bismuth corrosion, characterized in that: This method generates a uniform and dense protective multilayer oxide film of Al2O3, TiO2 and Cr2O3 on the surface of the high entropy alloy. The thickness of the Al2O3 oxide film is 200-500nm, the thickness of the TiO2 oxide film is 400-800nm, and the thickness of the Cr2O3 oxide film is 0.8μm-1.0μm.

5. The method of claim 4 for improving the FeNiCrAlTiSi by pre-oxidation treatment x A method for making a high entropy alloy resistant to lead-bismuth corrosion, characterized in that: When Si is contained in the high entropy alloy, a uniform and dense SiO2 oxide film is generated after pre-oxidation treatment, and the thickness of the SiO2 oxide film is 200 to 500 nm.

6. The method of claim 1 for improving the FeNiCrAlTiSi x A method for making a high entropy alloy resistant to lead-bismuth corrosion, characterized in that: The pre-oxidized high entropy alloy was heated to 550°C and the oxygen concentration was 1×10 -6 After being corroded for 3000h under the condition of wt.%, its surface still has a thin and dense multi-layer protective oxide film with a thickness not exceeding 5μm.

7. The method of claim 6 for improving the FeNiCrAlTiSi x A method for making a high entropy alloy resistant to lead-bismuth corrosion, characterized in that: Preferably, the thickness of the oxide film after etching for 3000 hours is 2 to 5 μm.

8. The method of claim 1 for improving the FeNiCrAlTiSi x A method for making a high entropy alloy resistant to lead-bismuth corrosion, characterized in that: The high entropy alloy treated by pre-oxidation has an oxygen concentration of 1×10 -3 ~1×10 -9 After being immersed in a static liquid lead-bismuth environment with a concentration of wt.% and a temperature of 350-600°C for 100-10000 hours, no intrusion of liquid lead-bismuth and no dissolution of matrix elements occurred.

Citation Information

Patent Citations

  • Liquid lead bismuth corrosion resistant high-entropy alloy and preparation method thereof

    CN115627405A

  • Liquid lead-bismuth eutectic corrosion and embrittlement resistant high-entropy alloy and preparation method thereof

    CN118422029A

Cited By

  • High-performance biphase nanostructure high-entropy alloy material and preparation method thereof

    CN120843923A